2008
DOI: 10.1001/archopht.126.10.1367
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Photodynamic Therapy and Intraocular Triamcinolone for Exudative Age-Related Macular Degeneration and Long-Term Chorioretinal Macular Atrophy

Abstract: Objective: To evaluate the long-term effect of intravitreal triamcinolone acetonide (IVT) treatment combined with photodynamic therapy (PDT) vs PDT alone for neovascular age-related macular degeneration.Methods: Prospective randomized study. Eighty-four patients were enrolled to receive PDT (n=41) or IVT treatment followed by PDT (n=43) within approximately a 7-to 15day interval. All patients were naive to treatment. At baseline and each follow-up visit at 3, 6, 12, and 24 months, measurement of best-corrected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Reduced choroidal perfusion is a known consequence of PDT therapy as treatment temporarily closes small-and medium-sized choroidal vessels as well as CNV. 9 Concurrent treatment with both steroids 10 and ranibizumab 11 prolong reduced choroidal perfusion. The PROTECT study 11 demonstrated reduced choroidal perfusion using indocyanine green angiography that persisted over 9 months of follow-up in 10 of 11 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced choroidal perfusion is a known consequence of PDT therapy as treatment temporarily closes small-and medium-sized choroidal vessels as well as CNV. 9 Concurrent treatment with both steroids 10 and ranibizumab 11 prolong reduced choroidal perfusion. The PROTECT study 11 demonstrated reduced choroidal perfusion using indocyanine green angiography that persisted over 9 months of follow-up in 10 of 11 patients.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Indocyanine green angiography studies 3,4 in those cases showed that there was a longer duration of choroidal hypoperfusion in patients with combined treatment. There have been some reports indicating that combined therapy decreases the number of PDT treatment and achieves a better visual outcome.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3][4][5][6] Prolonged choroidal hypoperfusion after combined treatment of PDT with either TA or anti-VEGF has been reported in previous reports [3][4][5] and is presumed to be a key factor in the delay of recurrence of CNV. It selectively photothromboses neovascular lesions.…”
mentioning
confidence: 86%
“…11 Second, the need for repeated injections is intensified by the indeterminacy of the results of the treatment. 12,13 Finally, the widespread use of Lucentis for treating AMD is hindered by its high cost-one injection costs about $2000, and a two-year course of treatment about $40,000. 14 The restriction of injections with the promise of increased visual acuity is associated with the synthesis of a new generation of inhibitors of growth factors of choroidal cells, such as VEGF Trap-Eye (aflibercept), EGFR, etc.…”
Section: Angiogenesis Inhibitorsmentioning
confidence: 99%